PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBANTUAN ARTICULATE STORYLINE 3 PADA MATA PELAJARAN PENDIDIKAN PANCASILA SISWA KELAS V SEKOLAH DASAR - Citra Dewi, Luh; Ngurah Arya Yudaparmita, Gusti; Ardiawan, I Ketut Ngurah (UHN IGB Sugriwa Denpasar, 2025)
This research aims to produce interactive learning media assisted by Articulate Storyline 3 in the Pancasila Education Subject for Class V Elementary School Students that is feasible and practical in increasing students' interest and enthusiasm for learning. The research method used is R&D with a 4-D development model which consists of four development stages, namely defining, designing, developing and disseminating. However, this research has only reached the development stage. ). The subjects of this research were 3 experts, 7 teachers, and 30% of class V elementary school students in each Gugus VII Elementary School, Sawan District. The research object is Interactive Learning Media Assisted by Articulate Storyline 3. The data analysis technique used is quantitative descriptive. The data collection methods used were observation, interviews, questionnaires. The research results obtained from Interactive Learning Media Assisted by Articulate Storyline 3 in the Pancasila Education Subject for Class V Elementary School Students can be said to be feasible and practical with the overall media suitability test results being 0.845833, material suitability being 0.825, and overall language suitability being 0.90625 and is included in the very high eligibility criteria. Meanwhile, the results of the practicality test by teachers and students obtained an overall practicality result by practitioners/teachers of 96.57142857 and an assessment by students of 96.2962963, meaning that the product developed was included in the very practical predicate/category classification.